2002
DOI: 10.1097/01.lab.0000021135.87203.92
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and an Angiogenic Response in the Partially Obstructed Rat Bladder

Abstract: SUMMARY: Previous molecular and blood flow studies performed on animal models of partial bladder outlet obstruction (PBOO) caused us to propose that bladder hypoxia/ischemia was a significant effector of the cellular and functional changes that occur in the bladder as a result of this condition. To confirm the occurrence of hypoxia in the partially obstructed bladder, we obtained rat bladders at increasing intervals following PBOO and measured biomarkers of hypoxia (intracellular formation of hypoxyprobe-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 32 publications
2
54
1
2
Order By: Relevance
“…In presence of vascular endothelial growth factor (VEGF), Ang-2 potentiates angiogenesis, whereas, in the absence of VEGF, the vessels may regress (2,6). Hypoxia initiates a change in Ang-1/Ang-2 ratio in favor of Ang-2 and results in vessel destabilization (7). VEGF is also induced by hypoxia and can drive the destabilized vessels toward angiogenesis.…”
mentioning
confidence: 99%
“…In presence of vascular endothelial growth factor (VEGF), Ang-2 potentiates angiogenesis, whereas, in the absence of VEGF, the vessels may regress (2,6). Hypoxia initiates a change in Ang-1/Ang-2 ratio in favor of Ang-2 and results in vessel destabilization (7). VEGF is also induced by hypoxia and can drive the destabilized vessels toward angiogenesis.…”
mentioning
confidence: 99%
“…17) Using this method, we have previously reported that a hypoxic condition exists within cerebral cortex in rats at 3, 9 and 24 h after MCA occlusion for 60 min, and proposed that plugging of microvasculature with granulocytes and platelets would be responsible for the hypoxic condition. 18) We also reported that tacrolimus attenuated cortical neuronal damage slightly at 9 h, with a significant effect at 24 h after MCA occlusion.…”
mentioning
confidence: 99%
“…Prolonged hypoxia, caused by inflammation, outlet obstruction, or vesical artery occlusion, is correlated with prolonged decreases in bladder blood flow, progressive bladder dysfunction, and, ultimately, bladder necrosis if blood flow is not restored (2-4, 37, 49). Vesical artery occlusion and decreased blood flow are also associated with significant bladder wall remodeling processes, including collagen deposition, urothelial barrier disruption, and production of proangiogenic factors and reactive oxygen species (2,12,31). Collectively, these observations suggest that the bladder is extremely sensitive to changes in blood flow, as even a modest reduction in blood flow leads to hypoxia, and prolonged changes in blood flow can cause bladder overactivity and remodeling.…”
Section: Discussionmentioning
confidence: 90%